2001
DOI: 10.1097/00007691-200110000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Thiopurine Methyltransferase Activity in Human Erythrocytes by High-Performance Liquid Chromatography: Comparison With the Radiochemical Method

Abstract: The current article describes a new assay to measure thiopurine methyltransferase (TPMT) activity from red blood cells. This method is based on the measurement of the reaction product 6-methylmercaptopurine (6-MMP) by high-performance liquid chromatography (HPLC). 6-MMP is extracted by ethyl acetate with recoveries of 85%, 80%, 80%, and 92% for 50, 250, 500, and 1,000 ng/100 microL packed red blood cells, respectively. 6-MMP was identified and measured by a Zorbax CN column installed in an HPLC system. The chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Moreover, the radiochemical assay in Singapore Chinese produced results that were approximately 3 times higher than those obtained from this study and Mayo Clinic. The TPMT activity values measured by HPLC were reported to be in close agreement with those measured by the radiochemical assay [19,22]. It has been shown that differences in assay conditions can cause significant differences in TPMT activity measured in different laboratories [5].…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the radiochemical assay in Singapore Chinese produced results that were approximately 3 times higher than those obtained from this study and Mayo Clinic. The TPMT activity values measured by HPLC were reported to be in close agreement with those measured by the radiochemical assay [19,22]. It has been shown that differences in assay conditions can cause significant differences in TPMT activity measured in different laboratories [5].…”
Section: Discussionsupporting
confidence: 58%
“…The lysate was centrifuged at 13,000 g for 10 min and the supernatant was used immediately for enzyme assays or stored at -85 • C; in this condition, the enzyme remains stable for several weeks. RBC TPMT activity was measured by a radiochemical method as previously described [15]. This procedure is based on the conversion of 6-MP to 6-methylmercaptopurine, using S-adenosyl-l-[methyl-3H]methionine as methyl donor.…”
Section: Analysis Of Tpmt Activitymentioning
confidence: 99%
“…When Aza enters the cell, it is transformed into 6-MP by an unknown cytosolic isoform of GST using GSH as a cosubstrate, which depletes the cytosolic GSH pool. After this, the following metabolic pathways are proposed for 6-MP: 1) methylation by thiopurine-methyltransferase to produce 6-methyl-mercaptopurine (Menor et al, 2001); 2) oxidation by XO to yield thiouric acid (Lewis and Olibier, 1977); 3) "the salvage pathway", whereby 6-MP would be incorporated into the intracellular purine nucleotide pool by the participation of hypoxantine phosphoribosyl transferase (Aarbakke et al, 1997); or 4) interaction with MPTP. The Aza/6-MP detoxificating role is attributable to thiopurine-methyl-transferase and XO-catalyzed reactions, whereas the antimitotic effect observed for both drugs corresponds to their incorporation into the 6-thioguanine nucleotide pool.…”
Section: Azathioprine Acts On Hepatocyte Mitochondria Involving Mapk 673mentioning
confidence: 99%